Glanz und Elend des Militärs am Beispiel von Generalmajor Friedrich Schirza - Zimmermann, Peter (Muzikološki zbornik, 2012)
The artistic creativity of Risto Savin as composer does not fit well with the prosaic profession of his alter ego Friedrich Schirza (1859-1948): he joined the Austro-Hungarian army in 1878 and left in 1918 as Major-General. Sources in the Vienna War Archives (Kriegsarchiv des österreichischen Staatsarchivs) allow us to draw an exact picture of his successful career as an artillery soldier and later as a senior official of the military-industrial complex.
Keywords: Avstro-Ogrska vojska; biografije; ruska fronta; Savin, Risto; slovenski skladatelji; svetovna vojna 1914-1918; vojaška kariera